2021
DOI: 10.1007/s41064-021-00163-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 3D Mapping and Modelling of Indoor Scenes with the Microsoft HoloLens: A Survey

Abstract: The Microsoft HoloLens is a head-worn mobile augmented reality device. It allows a real-time 3D mapping of its direct environment and a self-localisation within the acquired 3D data. Both aspects are essential for robustly augmenting the local environment around the user with virtual contents and for the robust interaction of the user with virtual objects. Although not primarily designed as an indoor mapping device, the Microsoft HoloLens has a high potential for an efficient and comfortable mapping of both ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…An interesting solution in room mapping is presented in [ 31 , 32 ]. The authors of these papers present the possibility of obtaining a digital representation of large indoor spaces in buildings using Hololens goggles.…”
Section: Theoretical Foundation and Related Workmentioning
confidence: 99%
“…An interesting solution in room mapping is presented in [ 31 , 32 ]. The authors of these papers present the possibility of obtaining a digital representation of large indoor spaces in buildings using Hololens goggles.…”
Section: Theoretical Foundation and Related Workmentioning
confidence: 99%
“…Thus, when mapping in unfurnished or less textured indoor environments, the transition area between different rooms may be a weak point in the mapping of the HoloLens, which is prone to large errors that affect the accuracy of the overall measurement data. Weinmann et al [ 45 , 46 ] demonstrated that the data acquired by the HoloLens is accurate enough to be used to reconstruct semantically rich and topologically correct indoor scene models. Jäger et al [ 47 ] in their study performed neural radiance fields (NeRFs) [ 48 , 49 , 50 ] 3D reconstruction using internal camera poses and images provided by the HoloLens, and revealed the potential of combining the HoloLens with NeRFs for highly detailed, colored, mobile 3D mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Low-cost 3D sensors such as RGBD cameras together with SLAM-based tracking provide the means for efficient and affordable mobile mapping systems with potential applications in fields like robotics and teleoperation (Stotko et al, 2019), documentation of cultural heritage (Teruggi and Fassi, 2022), forest monitoring as well as the mapping (Hou et al, 2023) and automatic modeling (Weinmann et al, 2021; of indoor building environments.…”
Section: Introductionmentioning
confidence: 99%